Identidades homosexuales y ciudad: Marginados negociando pactos de silencio - Segura-Gutiérrez, José Miguel (Prospectiva. Revista de Trabajo Social e Intervención Social, 2008)
This essay discusses the relationship between the city and gay subjectivities as collective space. The focus of interest is focused on examining the effects of the visibility of sexual dissidence is on the covenants and social arrangements which it creates and territorial states. As in turn, to cuts in terms of basic rights such individuals are victims, social coercion and self-construction, when their diverse sexual orientation and identity, is not considered a valid category of transformation, for the dismantling of institutionalized forms of domination and exclusion